# If S1, S2, S3 Be Respectively the Sums of N, 2n, 3n Terms of a G.P., Then Prove that S 2 1 + S 2 2 = S1 (S2 + S3). - Mathematics

If S1, S2, S3 be respectively the sums of n, 2n, 3n terms of a G.P., then prove that $S_1^2 + S_2^2$ = S1 (S2 + S3).

#### Solution

Let a be the first term and r be the common ratio of the given G.P.

$\text {Sum of n terms, } S_1 = a\left( \frac{r^n - 1}{r - 1} \right) . . . \left( 1 \right)$

$\text { Sum of 2n terms }, S_2 = a\left( \frac{r^{2n} - 1}{r - 1} \right)$

$\Rightarrow S_2 = a\left[ \frac{\left( r^n \right)^2 - 1^2}{r - 1} \right]$

$\Rightarrow S_2 = a\left[ \frac{\left( r^n - 1 \right)\left( r^n + 1 \right)}{r - 1} \right]$

$\Rightarrow S_2 = S_1 \left( r^n + 1 \right) . . . . \left( 2 \right)$

$\text { And, sum of 3n terms }, S_3 = a\left( \frac{r^{3n} - 1}{r - 1} \right)$

$\Rightarrow S_3 = a\left[ \frac{\left( r^n \right)^3 - 1^3}{r - 1} \right]$

$\Rightarrow S_3 = a\left[ \frac{\left( r^n - 1 \right)\left( r^{2n} + r^n + 1 \right)}{r - 1} \right]$

$\Rightarrow S_3 = S_1 \left( r^{2n} + r^n + 1 \right) . . . \left( 3 \right)$

$\text { Now, LHS }= \left( S_1 \right)^2 + \left( S_2 \right)^2$

$= \left( S_1 \right)^2 + \left[ S_1 \left( r^n + 1 \right) \right]^2 \left[ \text { Using } \left( 2 \right) \right]$

$= \left( S_1 \right)^2 \left[ 1 + \left( r^n + 1 \right)^2 \right]$

$= \left( S_1 \right)^2 \left[ 1 + r^{2n} + 2 r^n + 1 \right]$

$= \left( S_1 \right)^2 \left[ r^{2n} + r^n + 1 + r^n + 1 \right]$

$= \left( S_1 \right)\left[ S_1 \left( r^{2n} + r^n + 1 \right) + S_1 \left( r^n + 1 \right) \right]$

$= \left( S_1 \right)\left[ S_2 + S_3 \right] \left[ Using \left( 2 \right) and \left( 3 \right) \right]$

= RHS

Hence proved .

Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 20 Geometric Progression
Exercise 20.3 | Q 14 | Page 28